Broadband Degenerate Femtosecond OPO around 2060 nm - Wenlong Tian; Xianghao Meng; Ninghua Zhang; Jiangfeng Zhu; Zhaohua Wang; Zhiyi Wei (International Journal of Optics)
We demonstrate a broadband degenerate femtosecond optical parametric oscillator (OPO) around 2060 nm. Synchronically pumped by a commercially available 75.6 MHz Yb:KGW femtosecond laser, it is able to generate self-phase-locked 2 μm pulses with 82 mW output power and 3 dB bandwidth of 105 nm. The degenerate operation is naturally stable in free-running condition, with only 0.8% rms fluctuation in 3.5 hours. We also obtain broadband spectrum extending from 1600 nm to 2500 nm with the 3 dB bandwidth of 452 nm by increasing the intracavity power density.